(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
Appendiceal neoplasms are identified in 0.9 to 1.4% of appendiceal specimens, and the incidence is increasing. It has long been professed that neuroendocrine tumors (formerly carcinoids) are the most common neoplastic process of the appendix; recent data, however, has suggested a shift in epidemiology. Our intent is to distill the complex into an algorithm, and, in doing so, enable the surgeon to seamlessly maneuver through operative decisions, treatment strategies, and patient counseling. The algorithm for evaluation and treatment is complex, often starts from the nonspecific presenting complaint of appendicitis, and relies heavily on often subtle histopathologic differences.